The Study Influence of Cigarette Smoke by Using Laboratory Animals in Behavioral Test «Open Field» - Mustafa S Rauan (Journal of Global Pharma Technology, 2018)
Objective: All organs and systems of organs suffer from smoking without exception. On average, a smoker lives 10 years less than a non-smoker. In addition, given the harmfulness of second-hand smoke, there is no clear boundary between the smoker and the non-smoker. In this article we have examined the harm of polycyclic aromatic hydrocarbons as one of the harmful constituents of cigarette smoke. Methods: Depending on the drug and their concentration laboratory animals were divided into three groups. Number of laboratory animals in each group was 10. For first group was given only water. In second group during 4 weeks we used the passive smoking method. In third group during 4 weeks we used the passive smoking method. During the experiment for the testing animal behavior was used